The risk factors for tuberculosis in HIV-infected children with varying degrees of immunodeficiency - E. P. Eremenko (Association of Paediatric Allergists and Immunologists of Russia (APAIR), 2023)
Tuberculosis development risk factors of for children with HIV infection were studied, 26 children with combined HIV and tuberculosis examined, comparing to 50 children with local forms of tuberculosis, with no HIV-infection. All the kids from the first group were in perinatal contact in HIV. The comparative analysis of social, physical, biological and epidemiological factors between the groups showed that children having HIV contacted TB patients twice as frequently.